Cyprus : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper explores the economic consequences of aging and its impact on long-term fiscal sustainability for Cyprus. The study analyzes the potential macroeconomic impact of different approaches to deal with the fiscal costs of aging. It goes beyond a simple quantification of the fiscal impact by explicitly examining the trade-offs of alternative policies within the context of a general equilibrium overlapping generation framework. It is concluded that addressing the fiscal consequences of aging will require increasing the retirement age to 65 years, followed by further increases to keep up with demographic trends.